"Older and Wiser than the Schoolkids on the Bus": The Impact of Academic Transition on Learner Identity in an FE Setting - Gregory, Elizabeth (International Journal of Educational and Life Transitions, 2023)
Educational transitions occur throughout an individual’s academic career, but transitions from secondary school to college (which in England, generally take place at the age of 16) are currently under-represented in the literature. As students in England are now required to stay in education until the age of 18, it is crucial that this group of learners, typically aged 16–19, are appropriately supported in their transition to this next stage of their education. This paper presents some of the findings of the Learner, Identity and Transition Project (LITP), a case study exploring the impact of transition on learner identity in a college of further education in England. Through discussion of extracts from narrative interviews collected from students aged 16–19, the paper considers the academic and vocational qualifications available to students after leaving school, and the ways in which these are perceived. Findings suggest that whilst educational transitions can prompt worries about the academic and social changes involved, they are also a time of opportunity, offering the possibility of maturing and of forging a new, more authentic identity that participants believed was closer to their true self, as well as forming new friendship groups. Participants also demonstrated an awareness of the different values attached to academic and vocational qualifications. However, although this awareness impacted upon the ways in which participants narrated their experiences of transition, a more positive narrative around vocational qualifications as a means of progressing to higher education also emerged from the data.